FEASIBILITY STUDY ON ENVIRONMENTAL IMPACT ASSESSMENT FOR HYPOTHETICAL FLOW CONTROL PROJECTS USING FAZZY SET THEORY - SHEN, Yiyang; NAKATSUJI, Keiji (PROCEEDINGS OF HYDRAULIC ENGINEERING, 2004)
The concept of ‘environmental standard’ has been applied to coastal environmental impact assessment, EIA. The standard values have been determined for each water quality and for each divided coastal area. The achievement of improving water qualities depends on whether the values estimated by EIA are larger than the standard values or not. The uncertainly and complexity of the natural system, however, make it difficult for traditional approaches to come up with simple answers. To facilitate this integrative approach the basic concept of fuzzy set theory is introduced. In addition, the integrated evaluation function is also introduced. In the present study, the hypothetical Akashi Strait breakwater project is evaluated to test the usefulness of EIA used as a case study to examine the usefulness of this methodology: various models and data set are assembled and analyzed. Water qualities of COD, total nitrogen and total phosphorus are used to make EIA in Osaka Bay.